2008
DOI: 10.1007/s12272-001-2116-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of guanosine in rats following intravenous or intramuscular administration of a 1:1 mixture of guanosine and acriflavine, a potential antitumor agent

Abstract: A 1:1 mixture of acriflavine (ACF; CAS 8063-24-9) and guanosine is under evaluation in preclinical studies as a possible antitumor agent. Guanosine is known to potentiate the anti-cancer activity of ACF. We therefore investigated the pharmacokinetics of guanosine following administration of the ACF/guanosine mixture in rats. Rats were given guanosine (1 or 5 mg/kg) or ACF/guanosine (2 or 10 mg/kg) by i.v. bolus; or guanosine (3 or 15 mg/kg) or ACF/guanosine (6 or 30 mg/kg) by i.m. injection. We found that guan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Xanthine levels were higher at liver and kidneys, suggesting that these organs play an important role in the metabolism and possibly excretion of guanosine. This data is supported by a previous study, where [ 3 H]guanosine given via intramuscular was primarily found at animals kidney [ 61 ].…”
Section: Metabolism and Distribution Of Exogenous Guanosinesupporting
confidence: 90%
“…Xanthine levels were higher at liver and kidneys, suggesting that these organs play an important role in the metabolism and possibly excretion of guanosine. This data is supported by a previous study, where [ 3 H]guanosine given via intramuscular was primarily found at animals kidney [ 61 ].…”
Section: Metabolism and Distribution Of Exogenous Guanosinesupporting
confidence: 90%
“…The pharmacokinetics of ACF has been previously reported in the context of its antitumor activity. The published data point to a very fast plasma clearance of ACF by intravenous and intramuscular delivery ( Lee et al., 2007 ; Shin et al., 2008 ). ACF is approved for oral use as a systemic drug against urinary tract infections in Brazil; yet, data on oral bioavailability, pharmacokinetics, and lung concentration levels of ACF are not publicly available.…”
Section: Resultsmentioning
confidence: 99%
“…The discussion herein underscores the possibility for therapeutic intervention with either guanosine per se or with drugs that modulate guanosine. In this regard, guanosine could be delivered either intravenously or intramuscularly (Shin et al, 2008) or via intraperitoneal administration (Giuliani et al, 2012). Importantly, the results of the present study demonstrate that guanosine per se has little effect on basal arterial blood pressure or renal blood flow and therefore likely would be safe.…”
Section: Discussionmentioning
confidence: 99%